Superhero kindergarten. Superpower sleepover [videorecording (DVD)] - Lee, Stan, 1922-2018; Schwarzenegger, Arnold; Heyward, Andy; Nicieza, Fabian (NCircle Entertainment, 2022)
From legendary producer Stan Lee comes the tale of an (undercover) superhero teacher Mr. Armstrong, who is called on to train six extraordinary kindergarten students to use their superhero powers for good.